1998
DOI: 10.1021/jf980649b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydroxytyrosol Found in Extra Virgin Olive Oil on Oxidative DNA Damage and on Low-Density Lipoprotein Oxidation

Abstract: Hydroxytyrosol found in extra virgin olive oil strongly inhibited low-density lipoprotein oxidation stimulated by 2,2‘-azobis(2-amidinopropane) hydrochloride (AAPH), suggesting the ability to scavenge the AAPH-derived peroxyl radicals. Hydroxytyrosol inhibited iron-dependent phospholipid liposome peroxidation at low concentrations (IC50 = 50 ± 1.3 μM). In similar experiments, the calculated, IC50 values for other antioxidants compared are 1.5 ± 0.05 μM (carnosol), 2.25 ± 0.08 μM (carnosic acid), 65 ± 2.6 μM (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(70 citation statements)
references
References 38 publications
1
66
0
3
Order By: Relevance
“…The OOMWW phenolic fraction is characterized by a great complexity, as demonstrated by Bianco et al (2003); one of the most abundant and very interesting compounds from a nutritional point of view is hydroxytyrosol, which has been widely studied, demonstrating its antioxidant and beneficial health properties as well as its good bioavailability. Hydroxytyrosol scavenges free radicals (Visioli et al, 1999) and inhibits human low-density lipoprotein (LDL) oxidation (Aruoma et al, 1998;Casalino et al, 2002;Deiana et al, 1999). For economic reasons, OOMWW is usually concentrated in evaporation ponds and left to dry throughout the summer season (Borja et al, 1992;Benitez et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The OOMWW phenolic fraction is characterized by a great complexity, as demonstrated by Bianco et al (2003); one of the most abundant and very interesting compounds from a nutritional point of view is hydroxytyrosol, which has been widely studied, demonstrating its antioxidant and beneficial health properties as well as its good bioavailability. Hydroxytyrosol scavenges free radicals (Visioli et al, 1999) and inhibits human low-density lipoprotein (LDL) oxidation (Aruoma et al, 1998;Casalino et al, 2002;Deiana et al, 1999). For economic reasons, OOMWW is usually concentrated in evaporation ponds and left to dry throughout the summer season (Borja et al, 1992;Benitez et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…This is due, in part, to the relatively low content of PUFA and also to the high concentration of polyphenolic antioxidants, particularly in extra-virgin olive oil. The antioxidant activity of olive oil phenolic compounds, and in particular of oleuropein and its byproduct hydroxytyrosol, has been studied in many experimental models: with the use of transition metals; the chemically induced oxidation of LDL; ROS formation, for example the radicals superoxide and trichlormethylperoxylic, and hypochlorous acid (Aeschbach et al 1994;Salami et al 1995;Visioli et al 1995aVisioli et al , 1998Aruoma et al 1998). By estimating the antioxidant activity of these polyphenolic compounds on the basis of their ability to inhibit the formation of peroxides, it has been shown that hydroxytyrosol and caffeic and protocatechuic acids have a higher protective activity (Papadopoulos & Boskou, 1991).…”
Section: The Antioxidant Activity Of the Polyphenolic Compoundsmentioning
confidence: 99%
“…The reducing abilities of isolated compounds were determined according to the method of Aruoma et al (1998). The forty micro-liters of different concentrations of the compounds in distilled water were mixed with 160 µL of the mixture containing 0.5 mM CuCl 2 and 0.75 mM neocuproine in 10 mM phosphate buffer, pH 7.4.…”
Section: Determination Of Reduction Capacitymentioning
confidence: 99%